Self-Image of Sufistic Da'i on Social Media: Analysis of Sufism Content for Students on Social Media - Muhammad Munir; Abdulloh Hanif; Md.Mosaddek Billah (Mediakita, 2024)
Social media, such as Facebook, Instagram, Twitter, and other platforms, have changed the way we communicate, interact, and share information. Additionally, social media also has a significant impact on the way we view ourselves and others. The problem with a consumptive society is that Sufism is less interesting. This is because social media users need entertainment that is not monotonous with one goal, requiring a diversity of ways to reach God's love. This research method uses content analysis with data collection and coding methods for important content on Habib Husain bin Ja'far Al Hadar S.Fil.I., M.Ag YouTube channel. His YouTube channel is called "Jeda Nulis." This research uses analytical methods to explore data, display and validate data. The result of this research is that a Da’i Sufistic can combine Sufism and culture in an interesting way so that the mad’u watching can understand it. Apart from that, it combines an understanding of Sufism and tolerance, which can increase social harmony between religions. As well as preaching the importance of family in life. Lastly, it provides a construction that is easy and can attract someone to the goodness that we understand.